Pengembangan LKPD Terintegrasi STEAM-PjBL Pada Materi Larutan Penyangga Sma - Refitaniza Refitaniza; Effendi Effendi (Universitas Batanghari Jambi, 2022)
This research aims to develop teachig materials in the form of student worksheet intetgrated with Science, Technology, Engineering, Art and Mathematics – Project Based Learning (STEAM-PjBL) on Buffer Solution topic, and revealing the validity and practicality of the developed student worksheets. This research is R&D research with 4-D as the development model. This 4-D model has four stages, namely the define stage, the design stagethe develop stage and the disseminate stage. However the disseminate stage was not implemented. The research instrument used was a questionnaire in the form of a validity sheet and a practicality questionnaire. This student worksheet was validated by 5 expert including a chemistry lectures at FMIPA UNP and chemistry teachers at SMAN 6 Padang. The validation data were analyzed using the Aiken’s V scale while the practicality data were analyzed using a comparizon of the student’s value with the ideal maximum value of the student’s response. Based on the validation questionnaire that has been analyzed, it can be concluded that the student worksheet integrated with Science, Technology, Engineering, Art and Mathematics – Project Based Learning (STEAM-PjBL) on Buffer Solution topic is valid with a V value is 0,87 with valid category. While the practicality of teachers and students obtained NP value is 97% and 89% with a very practical category.